2019
DOI: 10.1109/tasc.2019.2894712
|View full text |Cite
|
Sign up to set email alerts
|

Current Flow and Flux Pinning Properties of YBCO Foam Struts

Abstract: The current flow and the flux pinning properties on struts of superconducting YBa2Cu3Ox (YBCO) foams are analyzed in detail in the temperature range 60 K ≤ T ≤ Tc. For this purpose, magnetization loops were measured on foam struts taken from various positions of a 5 × 2 × 2 cm 3 large foam sample prepared at RWTH Aachen. From these data, the critical current densities, jc, and the flux pinning forces, Fp = jc × B, were calculated and pinning force scaling diagrams Fp/Fp,max vs. h = Ha/Hirr were established. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

7
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 28 publications
(34 reference statements)
0
16
0
Order By: Relevance
“…On side (4), the maximum trapped field of 400 G is recorded. This is a surprising result, as we would have expected the maximum trapped field either on side (1) or on side (3), as position-dependent measurements of the properties of foam struts had shown increasing j c towards the bottom of the foam sample [30].…”
Section: Resultsmentioning
confidence: 84%
“…On side (4), the maximum trapped field of 400 G is recorded. This is a surprising result, as we would have expected the maximum trapped field either on side (1) or on side (3), as position-dependent measurements of the properties of foam struts had shown increasing j c towards the bottom of the foam sample [30].…”
Section: Resultsmentioning
confidence: 84%
“…On Side (4), the maximum trapped field of 400 G is recorded. This is a surprising result, as we would have expected the maximum trapped field either on Side (1) or on Side (3), as position-dependent measurements of the properties of foam struts had shown increasing jc towards the bottom of the foam sample [30]. Remarkably, there are many of the small, sharp peaks especially on Side (3), the bottom side of the foam sample.…”
Section: Resultsmentioning
confidence: 90%
“…From the bottom side, which was closest to the liquid source, the shape is found to change from the parabolic type (which contains more material on the ligands) to a more cusp-like type at the top face of the foam sample, which indicates the amount of liquid which was present during the processing. Previous work on flux pinning and critical currents in the foam sample [ 52 , 53 ] also revealed a clear dependence on the position within the original foam, and the TF measurements on all sides of a foam sample demonstrated that the top side was the weakest one [ 13 ]. Thus, this finding is another important issue for improving the properties of future YBCO foam samples.…”
Section: Results and Discussionmentioning
confidence: 99%